Não sou eu uma criança? diálogos com a infância negra abrigada - Souza, Quezia Alvim de (2024)
This study was developed with the aim of understanding the experiences produced and shared by black children living in a shelter for childhood in the city of Feira de Santana. The research is based on theoretical references that point out childhood as an important piece within the puzzle of human development. Regardless of the environment they are in, black children will always establish childhood experiences; the institutional shelter was chosen as the setting because it has historically and prejudicially been understood as the space designated for black and poor childhood in our country. The research sought to identify processes of cultural construction by the children inserted in the institution's context. The results indicate that the shelter provides a safe and protected environment for children; however, the lack of emotional attachment, and mainly the absence of playful moments or spaces for play negatively affect the children's childhood experience.